Proterozoic events recorded in quartzite cobbles at Jack Hills, Western Australia: New constraints on sedimentation and source of >4 Ga zircons - Grange, Marion; Wilde, Simon; Nemchin, Alexander; Pidgeon, Robert (Elsevier Science BV, 2010)
Rare heavy mineral bands within quartzite cobbles were identified in two conglomerate units within the Jack Hills belt, Western Australia. Seven zircon-bearing cobbles were analysed from one location (site 152) and three from another (site 154), both approximately 1 km west of the site where zircons in excess of 4 Ga are abundant (W74 ‘discovery’ site). Individual pebbles from the 152 site reveal three distinctive features, containing either zircons >3.0 Ga in age, <1.9 Ga in age or a range of ages from ∼1.2 to ∼3.6 Ga. Those from site 154 are more uniform, containing only zircons with ages between 3.1 and 3.9 Ga. Only one grain >4 Ga was discovered from the entire suite of pebbles, in contrast to the well-studied W74 site. A single detrital zircon with an age of 1220±42 Ma from location 152 is the youngest grain so far reported from sedimentary rocks at Jack Hills.It shows magmatic oscillatory zoning and thus implies at least two sedimentary cycles within the Proterozoic; requiring erosion of an igneous precursor, incorporation into a clastic sediment, induration and subsequent erosion and transport to be hosted in the conglomerate. The nearest source for rocks of this age is the Bangemall Supergroup in the Collier Basin, ∼100 km northeast in the Capricorn Orogen. This would imply tectonic interleaving of originally more extensive Bangemall rocks, possibly related to activity along the Cargarah Shear Zone that traverses the Jack Hills belt. The lack of >4.1 Ga zircons in the pebbles is highly significant, suggesting the immediate source of ancient zircons was no longer present at the Earth's surface. This equates with a general lack of ancient crystals noted in rocks that contain Proterozoic zircons from previous studies and implies that such grains diminish in number as earlier sedimentary rocks were successively recycled.